2004
DOI: 10.1002/adic.200490100
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrogen Salicylate Ion as Ligand. Complex Formation Equilibria with Dioxouranium(VI), Neodymium(III) and Lead(II)

Abstract: The complexation equilibria of the hydrogen salicylate ion, HL‐, have been studied, at 25 °C, by potentiometric measurements with a glass electrode in 1 M NaClO4 for uranyl and Nd(III) ions and in 3 M NaClO4 for Pb(II) ion. The ligand concentration (CL) was varied between 10‐3 and 0.05 M. In the system with U(VI) the concentrations ranged between: 10‐3 ≤ [U(VI)] ≤ 0.01 M, 0.5 ≤ CL /[U(VI)] ≤ 10 and 10‐2 d[H+]≤ 10‐5 M; for neodymium system: 2.10‐3 ≤ [Nd(III)] < 0.01, 1 ≤ CL /[Nd(III)] ≤ 10 and 10‐2 ≤ [H+] ≤ 10‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Their results indicated that, at pH 7.84, PbSal and Pb(Sal)2 2− should be the dominant species. Using the Furia and Porto [28] stability constants and a variant of the DeFord Hume equation [29][30][31], which is similar to the Lingane equation, we calculated that the shift in reduction potential should be closer to a factor of two times greater at pH 7.84 than what we observed. Furthermore, there should be a significant difference between pH 6.15 and pH 7.84.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Their results indicated that, at pH 7.84, PbSal and Pb(Sal)2 2− should be the dominant species. Using the Furia and Porto [28] stability constants and a variant of the DeFord Hume equation [29][30][31], which is similar to the Lingane equation, we calculated that the shift in reduction potential should be closer to a factor of two times greater at pH 7.84 than what we observed. Furthermore, there should be a significant difference between pH 6.15 and pH 7.84.…”
Section: Resultsmentioning
confidence: 72%
“…There are very few measurements of the stability constants between salicylate and Pb 2+ in the literature. Furia and Porto [28] investigated the interaction of Pb 2+ with hydrogen salicylate using potentiometric titration. These investigators measured the stability constants at a rather high ionic strength (3-M KClO 4 ) and extrapolated the constant to 0 ionic strength.…”
Section: Resultsmentioning
confidence: 99%
“…The cell arrangement was as formerly described [7]. The test solutions, stirred during titrations, were purified with a slow stream of nitrogen gas as reported in a previous work [8]. Glass electrodes were the same used in preceding evaluations [9]; they attained a constant potential within few minutes after the addition of the reagents and remained unchanged for several hours to within ± 0.1 mV.…”
Section: Apparatus and Reagentsmentioning
confidence: 99%
“…In the last years, we have been interested in a systematic study concerning the complexation of metal cations with 2-hydroxybenzoic acid (salicylic acid) and its derivatives [1][2][3][4][5][6][7][8]. Salicylic acid is both the simplest model for humic acids present in soil and an outstanding antirheumatic and antifungal substance; from this point of view its derivatives, such as 1-(2-hydroxyphenyl)ethanone (HY, Scheme 1), display the same properties.…”
Section: Introductionmentioning
confidence: 99%